A systematic approach for the analyses and design of jointed rock mass slopes against wedge and toppling failures: a case study of the stability of the abutments of the bridge across the Chenab River. Issue 1 (2nd January 2021) - Mantrala, Srinivas; Verma, A. K.; Sitharam, T. G.
ABSTRACT: The stability of jointed rock mass slopes in highly seismic areas is governed by the orientation of the joints with respect to the slope and the joint characteristics and the seismic accelerations. The paper presents a systematic approach for the analysis and design of jointed rock mass slopes against wedge and toppling failures in highly seismic areas. There are nine load cases to be considered in the analyses of slopes. To address the concerns on the uncertainty and variability of the geological data, the process of "Design as you go" was suggested. The bridge across the Chenab river gorge with a main arch span of 467m which is under construction is located in a highly seismically active zone. The approach proposed in this paper was successfully implemented in the stabilization of the abutments of the Chenab bridge which enhanced the confidence in the adequacy of slope stabilization measures.